2023
DOI: 10.1038/s41388-023-02687-6
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation of DDX21 promotes colorectal cancer metastasis via MCM5-dependent EMT pathway

Abstract: RNA binding proteins (RBPs) contributes to cancer progression, but the underlying mechanism reminds unclear. Here, we find that DDX21, a representative RBP, is highly expressed in colorectal cancer (CRC), which leads to CRC cell migration and invasion in vitro, and CRC to liver metastasis and lung metastasis in vivo. This effect of DDX21 on CRC metastasis is correlated to the activation of Epithelial-mesenchymal transition (EMT) pathway. Moreover, we reveal that DDX21 protein is phase separated in vitro and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…26,27 Given the commonality of abnormal cell cycle regulation in tumors, targeting MCM5 function holds promise as a potential strategy to inhibit the excessive proliferation of tumor cells. 20,21,23,[28][29][30] Importantly, we first reported that MCM5 promotes glioma cell U87 and U251 proliferation and resistance to TMZ, aligning with previous research indicating its role in cisplatin resistance in head and neck squamous cell carcinoma. However, further studies with the incorporation of more cell lines are necessary to confirm this scenario.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…26,27 Given the commonality of abnormal cell cycle regulation in tumors, targeting MCM5 function holds promise as a potential strategy to inhibit the excessive proliferation of tumor cells. 20,21,23,[28][29][30] Importantly, we first reported that MCM5 promotes glioma cell U87 and U251 proliferation and resistance to TMZ, aligning with previous research indicating its role in cisplatin resistance in head and neck squamous cell carcinoma. However, further studies with the incorporation of more cell lines are necessary to confirm this scenario.…”
Section: Discussionsupporting
confidence: 87%
“…15 It is a critical component of the CDC45-MCM-GINS helicase, a molecular apparatus responsible for unwinding template DNA during replication and serving as the foundation for the replisome. [16][17][18] Previous studies have found that MCM5 plays important roles in the progression of various cancers, including liver, lung, bladder, and colon cancers et al [19][20][21][22][23] Meanwhile, Jiang et al previously reported that the ubiquitination and degradation of MCM5 protein might impede the repair of DNA damage caused by cisplatin. 21 However, thus far, the expression, function and potential mechanisms of MCM5 in GBM chemotherapy resistance are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Phase separation is the main mechanism for the formation of membraneless compartments in cells and is involved in the regulation of cellular metabolism, signal transduction, gene expression and protein homeostasis. In recent years, researchers have found that phase separation and cancer are closely linked, by affecting DNA repair processes, transcriptional regulation as well as the assembly of important membrane-free compartments in cancer [ 23 , 33 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, another study revealed that the phase separation of DDX21 activates MCM5, thus triggering EMT signaling and modulating the colon cancer metastasis (Fig. 4 B)[ 143 ]. Besides, SGs are also involved in malignant invasion and metastasis.…”
Section: Deregulated Phase Separation In Cancermentioning
confidence: 90%